COVID-19: a catalyst for revitalizing mixed-use urban centers? The case of Paris. Issue 1 (2nd January 2023) - Machline, Elise; Pearlmutter, David; Cohen, Chen; Schwartz, Moshe
ABSTRACT: Since the mid-1990s, the French public authorities have changed regulations to allow commercial building conversions into housing. The COVID-19 crisis has affected the global economy, social connections, environmental trajectories and energy demand/supply. Countries have been considering measures to reduce the pandemic's long-term impact and since the beginning of 2020, national governments have recommended that companies facilitate remote work. Thus, COVID-19 has prompted some office building depopulation. With working from home expected to continue after the pandemic, due to technological, environmental and economic considerations, there is a growing impetus to convert empty office space into residential uses. The present research aims, through the Parisian case study, to consider the impacts of the pandemic and the acceleration of homeworking. Using a mixed qualitative and quantitative methodology, the study aims to (1) critically analyse the policy tools implemented by the Paris municipality following the COVID-19 pandemic to accelerate commercial building conversions and (2) evaluate the potential for such conversions, considering former policies. We found that adaptive reuse policies have been implemented following the beginning of the COVID-19 crisis. However, according to the collected data, conversion potential is limited, due to the continuing demand for office space despite the changes and economic considerations.